1996
DOI: 10.1002/(sici)1099-1298(199605)6:2<77::aid-casp354>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Persuasion Strategies Applied in Psychosocial Rehabilitation

Abstract: Theoretically one of the most important questions in applied psychology is how people influence and control each other. What theoretical concepts can be used to explain these influences? Learning theory explanations have been popular in psychology, but other alternatives are also possible. In this article, rehabilitation is analysed through interactional persuasion strategies. Six strategies are proposed: coercion, threat, offer, guidance, appeal and appreciation. Each strategy corresponds to a specific atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…While consistent findings on the effectiveness of foot-in-the-door and door-in-the-face techniques is encouraging, the number of different persuasion taxonomies available in the literature makes it difficult to build an empirical understanding of the vast array of potential avenues for persuasion. In an effort to draw disparate streams of persuasion research together, Ojanen (1996) reviewed the literature and suggested that six persuasion strategies were sufficient to cover the large number of strategies in the literature: coercion, threat, offer, guidance, appeals, and appreciation. These six strategies map loosely to the proactive influence tactics as follows: coercion with pressure/legitimating, threat with pressure/ legitimating, offer with collaboration, guidance with rational persuasion, appeals with inspirational and personal appeals, and appreciation with ingratiation.…”
Section: Consistency/commitmentmentioning
confidence: 99%
See 4 more Smart Citations
“…While consistent findings on the effectiveness of foot-in-the-door and door-in-the-face techniques is encouraging, the number of different persuasion taxonomies available in the literature makes it difficult to build an empirical understanding of the vast array of potential avenues for persuasion. In an effort to draw disparate streams of persuasion research together, Ojanen (1996) reviewed the literature and suggested that six persuasion strategies were sufficient to cover the large number of strategies in the literature: coercion, threat, offer, guidance, appeals, and appreciation. These six strategies map loosely to the proactive influence tactics as follows: coercion with pressure/legitimating, threat with pressure/ legitimating, offer with collaboration, guidance with rational persuasion, appeals with inspirational and personal appeals, and appreciation with ingratiation.…”
Section: Consistency/commitmentmentioning
confidence: 99%
“…Leader indicates that each of two or more choices is equally valuable, and equally likely to lead to positive consequences. Ojanen (1996) Describing Single Positive Choice…”
Section: Blockingmentioning
confidence: 99%
See 3 more Smart Citations